2013
DOI: 10.1002/ptr.5062
|View full text |Cite
|
Sign up to set email alerts
|

Dark Chocolate: An Obesity Paradox or a Culprit for Weight Gain?

Abstract: Obesity remains a major public health challenge, and its prevalence is dramatically increasing. Diet and exercise are typically recommended to prevent and manage obesity; however, the results are often conflicting. Polyphenols, a class of phytochemicals that have been shown to reduce the risk factors for diabetes type II and cardiovascular diseases, are recently suggested as complementary agents in the management of obesity through several mechanisms such as decreasing fat absorption and/or fat synthesis. Dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…While several short-term (i.e., 2–8 weeks) studies have examined changes in body weight following consumption of chocolate, only one study, performed in overweight and obese women, has compared the effects of chocolate against non-chocolate intake specifically on changes in body weight and composition during energy restriction [34,35]. In this feasibility study, inclusion of a dark chocolate or non-chocolate sweet snack as part of the diet resulted in losses in fat mass, body weight and body fat percentage, with no significant differences between the two snack groups.…”
Section: Negative Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…While several short-term (i.e., 2–8 weeks) studies have examined changes in body weight following consumption of chocolate, only one study, performed in overweight and obese women, has compared the effects of chocolate against non-chocolate intake specifically on changes in body weight and composition during energy restriction [34,35]. In this feasibility study, inclusion of a dark chocolate or non-chocolate sweet snack as part of the diet resulted in losses in fat mass, body weight and body fat percentage, with no significant differences between the two snack groups.…”
Section: Negative Effectsmentioning
confidence: 99%
“…In this feasibility study, inclusion of a dark chocolate or non-chocolate sweet snack as part of the diet resulted in losses in fat mass, body weight and body fat percentage, with no significant differences between the two snack groups. However, the sample size of this pilot study was small, and outcomes were limited to body composition and without further exploration of biomarkers of metabolic health [34]. …”
Section: Negative Effectsmentioning
confidence: 99%
“…Therefore, 36 a transport system is required, called the carnitine shuttle system, catalyzed by carnitine vii.…”
mentioning
confidence: 99%
“…Moreover, another study found that smelling or ingesting 30 g of dark chocolate suppresses the appetite through the involvement of decreased ghrelin, the hunger hormone [27]. However, dark chocolate's effect on satiety might be a function of its intense flavor from its high cocoa content and high fat content that increases gastrointestinal transit time [28].…”
Section: Discussion Chocolate Consumption Chocolate Health Beliefs mentioning
confidence: 99%